Submandibular Space Infection: A Wake-Up Call for Parents and Caregivers - Jha, Divya; Dikshit, Parajeeta; Limbu, Senchhema; Malla, Manisha; Tripathi, Roshila (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Fascial space infection is the most prevalent infection and is regarded as a potentially life-threatening condition that can be caused by poor dental hygiene and other etiological variables, like tooth infections and compromised immunity. Fascial space infections of the head and neck region are usually odontogenic in origin and submandibular space infections is the most commonly encountered. The present case report describes a child with submandibular space infection with decreased mouth opening secondary to carious primary right mandibular second molar. The patient was kept under intravenous fluids, antibiotics and analgesics for 5 days. After discharge, pulpectomy of the offending carious tooth was performed followed by placement of stainless steel crown in subsequent dental visits.